PPP in the Medium Run Despite Oil Shocks: The Case of Norway - Q. Farooq Akram (Norges Bank, 2002)
Existing studies generally reject purchasing power parity (PPP) on datasets from countries that have been affected by large real shocks, including Norway. However, we offer strong evidence of PPP between Norway and its trading partners during the post-Bretton Woods period, in which the Norwegian economy has experienced numerous real shocks such as discoveries of large petroleum reserves and oil price shocks. In particular, the behaviour of the Norwegian real and nominal exchange rates appears remarkably consistent with the PPP theory. Moreover, convergence towards PPP is relatively fast; the half-life of a deviation from parity is just about 1.5 years. We show that such deviations are eliminated by adjustments in the nominal exchange rate and we offer some explanations for the relatively fast convergence towards PPP.
hdl:11250/2498650
Keywords: C22; C32; C51; F31; F41; 330; PPP; purchasing power parity; real exchange rate; cointegration analysis